Analisis Penerapan Manajemen Rantai Pasok (Supply Chain) Minyak Nilam Pada PT. XYZ - Ningtiyas, Aaliya Ratna; Kurniasari, Kurniasari; Dewi, Galuh Puspa; Ramadhani, Nurul Suci; Ridwan, Muhammad; Husyairi, Khoirul Aziz (Innovative: Journal Of Social Science Research, 2024)
This research analyses the application of patchouli oil Supply Chain Management in PT. XYZ, a company engaged in the production and export of essential oils. The research was conducted using a qualitative descriptive method based on primary and secondary data. The research results show that the Supply Chain of PT. XYZ involves local farmers as raw material suppliers, which are then processed through the distillation process before being distributed to domestic and international consumers. Three main flows in the Supply Chain, namely product flow, finance, and information, are effectively managed to ensure product efficiency and quality. Pre-order-based ordering system and just-in-case (JIC) inventory approach are applied to meet market demand. With this strategy, the company has succeeded in maintaining good relationships with farmers, consumers, and logistics partners, as well as optimizing the production and distribution process. This research provides an important overview of Supply Chain Management that can increase the efficiency and profitability of the essential oil industry.